The impact of narration, sentiment, and emotional modulation on economic of decision-making: a multidisciplinary study - Zubiel, Magdalena; Waligórska, Hanna (Oeconomica Jadertina, 2023)
The article delves into the interplay between narration, sentiment, and decision-making processes, particularly within the realm of economic choices. Emphasizing the pivotal role of message content, the authors present a hypothesis depicting the profound impact of narration, characters, and sentiment in the communication process. These components wield significant influence over the emotional facets of decision-making, influencing the process or prompting alterations to initial decisions. Critically challenging established economic paradigms, the article underscores the indispensable emotional dimension inherent in communication. Drawing upon the scholarly contributions of eminent figures like Robert J. Shiller, the authors synthesize insights from psychology and neurobiology, unraveling the manipulative essence inherent in narration. In the theoretical section, the article also references Uri Hasson's theories and research on brain synchronization during the communication process. The practical segment of the article substantiates these claims through the presentation of findings from neuropsychological studies. The study confirms the hypothesis that narratives infused with high sentiment resulting from emotional interactions, following a cause-and-effect structure with a visible beginning, development, and end, lead to better synchronization and intensify neuronal responses. The structure, plot shaping, and sentiment in messages, influenced by word choice, shape narrative economy and impact cognitive costs in decision-making. The obtained results confirm that precisely tailored narration effectively reduces cognitive costs associated with the decision-making process. This validates the authors' hypothesis, opening up space for research replication and falsification of the results obtained.